Membangun Kesadaran dan Implementasi Moderasi Beragama Di Kalangan Generasi Milenial Desa Mulyosari Kecamatan Pasir Sakti Lampung Timur - Aliyandi A. Lumbu; Dewi Asiyatus Shofuroh; Deppy Nurleni; Anis Marlita; Nurul Syamsiah; Putra Faris Sabqi; Silvia Imroatun Hasanah; Waedatul Riski Mauliana (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2024)
Religious moderation, rooted to the Arabic concept "al-wasathiyah", is an important approach to addressing diversity. Its application aims to provide a real-life example of how religious moderation can be manifested in the modern age, and it explains how to reinforce religious moderation in the midst of differing views in Islam. In the village of mulyosari, practicing islamic moderation harmoniously works. The celebration of the glorious hut of mulyosari isa concrete proof, in which all citizens are involved without regard for their religious or islamic organization. This qualitative study presents detailed and narrative results from various perspectives, showing the positive effect of moderate religious application in the mulyosari village. Such activities as communal prayer involving an entire community of diverse religious backgrounds, as well as praying, provide insight into religious moderation and enhance cooperation between islamic organizations